2020
DOI: 10.4218/etrij.2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

A network traffic prediction model of smart substation based on IGSA‐WNN

Abstract: The network traffic prediction of a smart substation is key in strengthening its system security protection. To improve the performance of its traffic prediction, in this paper, we propose an improved gravitational search algorithm (IGSA), then introduce the IGSA into a wavelet neural network (WNN), iteratively optimize the initial connection weighting, scalability factor, and shift factor, and establish a smart substation network traffic prediction model based on the IGSA‐WNN. A comparative analysis of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The conventional GSA, while effective in searching for algorithmic parameters in the RBFNN, exhibits relatively slow updates of gravitational coefficients and iteration speeds. In order to expedite this process, we propose an IGSA as a means to overcome these limitations [60]. The objective of IGSA is to enhance the gravitational coefficient, update speed formula, and position update formula of the regular GSA.…”
Section: Lagrange's Ahm-critic Coefficient Couplingmentioning
confidence: 99%
“…The conventional GSA, while effective in searching for algorithmic parameters in the RBFNN, exhibits relatively slow updates of gravitational coefficients and iteration speeds. In order to expedite this process, we propose an IGSA as a means to overcome these limitations [60]. The objective of IGSA is to enhance the gravitational coefficient, update speed formula, and position update formula of the regular GSA.…”
Section: Lagrange's Ahm-critic Coefficient Couplingmentioning
confidence: 99%
“…At present, the main processing method for industrial control system network misuse detection is in order to use deep learning network to learn the characteristics of industrial control system network data, and complete the classification by Softmax classifier. Early researchers mainly used Wavelet Neural Network (WNN) and Deep Neural Network (DNN) to establish misuse detection models [5,6]. However, they find that there are some problems in establishing network misuse detection models of industrial control systems by using such networks.…”
Section: Explainationsmentioning
confidence: 99%
“…11 With the development of network measurement technology, researchers have found that network traffic has a long-term correlation, namely, self-similarity, which cannot be dealt with by these traditional linear prediction model models. The nonlinear prediction model include support vector machine (SVM), 12 least square support vector machine (LSSVM), 13,14 artificial neural networks, [15][16][17][18] and gray model. 19 In recent years, some network traffic models based on deep learning model are proposed and achieve some progress.…”
Section: Introductionmentioning
confidence: 99%